Influence of natural convection on gold nanorods-assisted photothermal treatment of bladder cancer in mice. (1st January 2020) - Ooi, Ean H.; Popov, Viktor; Alfano, Massimo; Cheong, Jason K. K.
Abstract: Background: The thermally-induced urine flow can generate cooling that may alter the treatment outcome during hyperthermic treatments of bladder cancer. This paper investigates the effects of natural convection inside the bladder and at skin surface during gold nanorods (GNR) - assisted photothermal therapy (PTT) of bladder cancer in mice. Methods: 3D models of mouse bladder at orientations corresponding to the mouse positioned on its back, its side and its abdomen were examined. Numerical simulations were carried out for GNR volume fractions of 0.001, 0.005 and 0.01% and laser power of 0.2 and 0.3 W. Results: The obtained results showed that cooling due to natural convection inside the bladder and above the skin depends on the mouse orientation. For a mouse positioned on its back, on its side or on its abdomen, the maximum temperature achieved inside the tumour at 0.001% GNR volume fraction and 0.2 W laser power was 55.2°C, 50.0°C and 52.2°C, respectively compared to 56.8°C when natural convection was not considered. The average thermal gradients when natural convection was considered were also lower, suggesting a more homogenous temperature distribution. Conclusions: Natural convection inside the bladder can be beneficial but also detrimental to GNR-assisted PTT depending on the level of heating. At low levels of heating due to low GNR volume fraction and/or laser power, flow inside the bladder may dissipate heat from the targeted tissue; making the treatment ineffective. At high levels of heating due to high GNR volume fraction and/or laser power, cooling may prevent excessive thermal damage to surrounding tissues.